Quello oscuro oggetto del desiderio. La casa a Ghiffa di Aldo Rossi, una collezione di promesse - Moschetti, Vincenzo (Firenze Architettura, 2019)
Aldo Rossi began the transformation of the 'Ghiffa House' on Lake Maggiore from an old mill on the day of San Faustino in 1989. It represented the dream of a lost villa, of something which had already become mythical among faded Polaroids and recovered sketches. Where have the colours, the memories, the objects and their dust gone? They are buried figures which re-emerge in a cinematographic construction of shots between desire and architecture, in that place – Ghiffa – which marked both the beginning and the end of an artist's life.